Microglial Sirtuin 2 Shapes Long-Term Potentiation in Hippocampal Slices - Sa de Almeida, Joana; Vargas, Mariana; Fonseca-Gomes, João; Tanqueiro, Sara Ramalho; Belo, Rita F.; Miranda-Lourenço, Catarina; Sebastião, Ana M.; Diógenes, Maria José; Pais, Teresa F. (Frontiers in Neuroscience, 2020)
Microglial cells have emerged as crucial players in synaptic plasticity during development and adulthood, and also in neurodegenerative and neuroinflammatory conditions. Here we found that decreased levels of Sirtuin 2 (Sirt2) deacetylase in microglia affects hippocampal synaptic plasticity under inflammatory conditions. The results show that long-term potentiation (LTP) magnitude recorded from hippocampal slices of wild type mice does not differ between those exposed to lipopolysaccharide (LPS), a pro-inflammatory stimulus, or BSA. However, LTP recorded from hippocampal slices of microglial-specific Sirt2 deficient (Sirt2-) mice was significantly impaired by LPS. Importantly, LTP values were restored by memantine, an antagonist of N-methyl-D-aspartate (NMDA) receptors. These results indicate that microglial Sirt2 prevents NMDA-mediated excitotoxicity in hippocampal slices in response to an inflammatory signal such as LPS. Overall, our data suggest a key-protective role for microglial Sirt2 in mnesic deficits associated with neuroinflammation.